2020
DOI: 10.21873/invivo.12083
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Immune-related Adverse Events and Clinical Outcome Following Nivolumab Treatment in Patients With Metastatic Renal Cell Carcinoma

Abstract: Background/Aim: Immune-related adverse events (irAEs) are associated with the efficacy of immune-checkpoint inhibitors in patients with melanoma and non-small cell lung cancer. We therefore evaluated the relationship between irAEs and nivolumab efficacy against metastatic renal cell carcinoma. Patients and Methods: The medical records of 53 consecutive patients were reviewed and analyzed. Results: Median overall survival was significantly better in patients who showed irAEs at any time compared to patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Previous studies reported a relationship between irAEs and the antitumor effect of ICIs in malignant melanoma and non-small cell lung cancer, resulting in significant prolongation of OS [ 20 , 21 ]. A similar report has been published for RCC [ 22 ]. This case may also suggest an association between an irAE and complete response to nivolumab and ipilimumab.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies reported a relationship between irAEs and the antitumor effect of ICIs in malignant melanoma and non-small cell lung cancer, resulting in significant prolongation of OS [ 20 , 21 ]. A similar report has been published for RCC [ 22 ]. This case may also suggest an association between an irAE and complete response to nivolumab and ipilimumab.…”
Section: Discussionsupporting
confidence: 70%
“…The correlation between irAEs and patient outcome has been recently described for different cancers [ 10 , 37 , 38 ]. The occurrence of irAEs has been found to be associated with favorable outcomes in melanoma [ 21 , 22 , 23 ], NSCLC [ 24 , 25 , 26 ] and, with only a few studies available, also in mRCC [ 27 , 28 , 29 ]. These studies corroborate the hypothesis of a direct link between antitumor response and auto-immune reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of this research irAEs have been proposed as potential clinical markers to predict response to ICI. This relationship, although documented in studies regarding non-small cell lung cancer (NSCLC) and melanoma [ 21 , 22 , 23 , 24 , 25 , 26 ] has been less studied in RCC [ 27 , 28 , 29 ]. Moreover, current data on the impact of specific types of irAEs on outcomes are not entirely consistent.…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out from the results of our meta-analysis that, although ICIs increased the adverse events, the rates were actually low and acceptable. Although immunotherapy had increased the rates of irAEs, to a certain extent, the occurrence of immune-related events may be positively correlated with the therapy’s efficacy and the patient’s prognosis ( 66 , 67 ). When focusing on the anti-tumor effects of ICIs, we should also pay attention to the occurrence of irAEs when ICIs are applied ( 68 ).…”
Section: Discussionmentioning
confidence: 99%